Description of the Dependence of Craniometric Parameters on the Severity of Myopia in Children with Myopia (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
According to the World Health Organization (WHO), myopia has spread to 1.6 billion people in recent years and is predicted to reach 5 billion by 2050. Carrying out a number of studies in case of dysfunction of a particular organ allows us to determine changes in special topographic areas of the musculoskeletal system against the background of diseases. Craniometry is considered one of the important sections of anthropometry, and the determination of anatomical changes in craniometric parameters is of great importance for theoretical and practical medicine. Today, craniometric studies are actively used in scientific research in otorhinolaryngology, neurology, dentistry and ophthalmology and help find reasonable solutions to the problems of these areas. One of these tasks is to find a solution for studying the formation of the eyeball with varying degrees of severity of myopia, which is the most common refractive anomaly in a growing body. There is a need in the world to determine the theories of cooperative development of organs and the topographical areas in which they are located and which of them are the main ones. In recent years, the incidence of myopia has been increasing worldwide, reaching 96% among the young population of some countries. However, in children born with myopia, little has been studied about the formation processes in the organs and systems of the growing organism, in particular, what obstacles arise in the development and growth of the orbit. Establishing parallels in the development of the organ of vision and the eyeball helps to develop measures aimed at preventing developmental defects that can be observed in postnatal ontogenesis. The prevalence of myopia among children and not always timely diagnosis can negatively affect the child’s quality of life, lead to retinal detachment and disability from childhood or early working age.